A study on the meaning and structure of an English fairy-tale: A systemic functional analysis = Nghiên cứu về ngữ nghĩa và cấu trúc của một câu truyện cổ tiếng Anh theo quan điểm của ngữ pháp chức năng hệ thống. M.A. Thesis Linguistics: 60 22 15 - Nguyễn, Thị Lan (University of Languages and International Studies, 2017)
M.A. Thesis. English Linguistics -- University of Languages and International Studies. Vietnam National University, Hanoi, 2011